TET1 Isoforms Have Distinct Expression Pattern, Localization and Regulation in Breast Cancer - Alzahayqa, Mahmoud; Jamous, Abrar; Khatib, Areej A. H.; Salah, Zaidoun (Frontiers in Oncology, 2022)
TET1 regulates gene expression by demethylating their regulatory sequences through the conversion of 5-methylcytosine to 5-hyroxymethylcytosine . TET1 plays important roles in tissue homeostasis. In breast cancer, TET1 was shown to play controversial roles. Moreover, TET1 has at least two isoforms (long and short) that have distinct expression pattern and apparently different functions in tissue development and disease including breast cancer. We hypothesized that TET1 isoforms have different expression patterns, localization and regulation in different types of breast cancer. To prove our hypothesis, we studied the expression of TET1 isoforms in basal and luminal breast cancer cell lines, as well as in basal and luminal breast cancer animal models. We also studied the effect of different hormones on the expression of the two isoforms. Moreover, we assessed the distribution of the isoforms between the cytoplasm and nucleus. Finally, we overexpressed the full length in a breast cancer cell line and tested its effect on cancer cell behavior. In this study, we demonstrate that while Estrogen and GnRH downregulate the expression of long TET1, they lead to upregulation of short TET1 expression. In addition, we uncovered that luminal cells show higher expression level of the long isoform. We also show that while all TET1 isoforms are almost depleted in a basal breast cancer animal model, the expression of the short isoform is induced in luminal breast cancer model. The short form is expressed mainly in the cytoplasm while the long isoform is expressed mainly in the nucleus. Finally, we show that long TET1 overexpression suppresses cell oncogenic phenotypes. In conclusion, our data suggest that TET1 isoforms have distinct expression pattern, localization and regulation in breast cancer and that long TET1 suppresses oncogenic phenotypes, and that further studies are necessary to elucidate the functional roles of different TET1 isoforms in breast cancer.